Long-term transplant outcomes after allogeneic hematopoietic transplant in pediatric patients with hematological malignancies are influenced by severe chronic graft vs. host disease and immune reconstitution - Molina, Blanca; González-Vicent, Marta; Lopez, Ivan; Pereto, Alba; Ruiz, Julia; Ramirez, Manuel; Díaz, Miguel A. (Frontiers in Pediatrics, 2022)
Long-term follow-up studies are crucial to ensure surveillance and intervention for late complications after allogeneic stem cell transplantation, but they are scarce on the pediatric population. This study aims to analyze risk factors for long-term transplant outcomes. We report a landmark analysis of 162 pediatric patients who underwent allogeneic transplantation between 1991 and 2016, and survived for at least 12 months after the transplant. With a median follow-up time of 10 years for the survivors, the probability of disease-free survival (DFS) and overall survival (OS) is 81 ± 3 and 88 ± 2%, respectively. Variables that influenced DFS in the univariate analysis were: disease phase (early phase 87 ± 3% vs. advanced phase 74 ± 5%; p = 0.04), acute graft vs. host disease (aGvHD; yes 73 ± 5% vs. no 87 ± 3%; p = 0.038), severe chronic GvHD (cGvHD; yes 41 ± 13% vs. no 85 ± 3%; p = 0.0001), and CD4+ lymphocytes 2 years after the transplant (above the median of 837/μl 98 ± 2% vs. below the median 82 ± 6%, p = 0.026). However, in the multivariate analysis, the only variable that influenced DFS was presence of severe chronic GvHD (yes vs. no, HR 6.25; 95% CI, 1.35–34.48; p = 0.02). Transplant strategies should aim to reduce the risk of severe cGvHD. Immune reconstitution surveillance may help clinicians to better deal with late transplant complications.